Effectiveness of Warm Foot Bath Therapy in Managing Hypertension: Community-Based Application in Sepakat Bersama Village, Barito Kuala - Nurhanifah, Dewi; Yasin, Asrur; Zinan, Rabiatul; Mutia, Mutia; S, Nessa A.P.; Azizah, Nor; A, Nugraha P.P (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Hypertension is a chronic non-communicable disease that can lead to severe complications such as stroke and heart problems. A non-pharmacological approach like warm foot soak therapy offers a simple and effective method for lowering blood pressure. This study aimed to evaluate the impact of warm foot soak therapy on reducing blood pressure in hypertensive patients. Using a pre-experimental design with a one-group pretest-posttest method, 13 participants with mild to moderate hypertension underwent a single 15-minute session of warm foot soak therapy. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. On average, systolic blood pressure dropped from 180.15 mmHg to 157.77 mmHg, while diastolic pressure decreased from 101.08 mmHg to 96.08 mmHg. Most participants (92.3%) experienced a reduction in blood pressure. The findings indicate that warm foot soak therapy is effective in lowering blood pressure and can serve as a practical non-pharmacological nursing intervention in community health settings.